Cisplatin-induced nephrotoxicity and targets of nephroprotection: an update - dos Santos, Neife Aparecida Guinaim; Carvalho Rodrigues, Maria Augusta; Martins, Nadia Maria; dos Santos, Antonio Cardozo (Archives of toxicology, 2012)
Cisplatin is a highly effective antitumor agent whose clinical application is limited by the inherent nephrotoxicity. The current measures of nephroprotection used in patients receiving cisplatin are not satisfactory, and studies have focused on the investigation of new possible protective strategies. Many pathways involved in cisplatin nephrotoxicity have been delineated and proposed as targets for nephroprotection, and many new potentially protective agents have been reported. The multiple pathways which lead to renal damage and renal cell death have points of convergence and share some common modulators. The most frequent event among all the described pathways is the oxidative stress that acts as both a trigger and a result. The most exploited pathways, the proposed protective strategies, the achievements obtained so far as well as conflicting data are summarized and discussed in this review, providing a general view of the knowledge accumulated with past and recent research on this subject.